2014
DOI: 10.1111/pbi.12201
|View full text |Cite
|
Sign up to set email alerts
|

Improved soybean oil quality by targeted mutagenesis of the fatty acid desaturase 2 gene family

Abstract: SummarySoybean oil is high in polyunsaturated fats and is often partially hydrogenated to increase its shelf life and improve oxidative stability. The trans-fatty acids produced through hydrogenation pose a health threat. Soybean lines that are low in polyunsaturated fats were generated by introducing mutations in two fatty acid desaturase 2 genes (FAD2-1A and FAD2-1B), which in the seed convert the monounsaturated fat, oleic acid, to the polyunsaturated fat, linoleic acid. Transcription activator-like effecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
269
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 484 publications
(279 citation statements)
references
References 26 publications
2
269
0
8
Order By: Relevance
“…Both TALENs and CRISPRCas9 have been used to modify multiple alleles within hexaploid bread wheat to confer heritable resistance to powdery mildew (Wang et al 2014b). In another study, TALENs were used to knock out nonessential genes in the fatty acid metabolic pathway in soybean to generate a simplified plant cell with reduced metabolic components (Haun et al 2014). Of special note, two recent reports showed that purified nuclease proteins can be introduced directly into plant protoplasts, enabling the introduction of germline-transmissible modifications that are virtually indistinguishable from naturally occurring (Luo et al 2015;Woo et al 2015).…”
Section: Genome-editing Applications Engineering Cell Lines and Organmentioning
confidence: 99%
“…Both TALENs and CRISPRCas9 have been used to modify multiple alleles within hexaploid bread wheat to confer heritable resistance to powdery mildew (Wang et al 2014b). In another study, TALENs were used to knock out nonessential genes in the fatty acid metabolic pathway in soybean to generate a simplified plant cell with reduced metabolic components (Haun et al 2014). Of special note, two recent reports showed that purified nuclease proteins can be introduced directly into plant protoplasts, enabling the introduction of germline-transmissible modifications that are virtually indistinguishable from naturally occurring (Luo et al 2015;Woo et al 2015).…”
Section: Genome-editing Applications Engineering Cell Lines and Organmentioning
confidence: 99%
“…Examples of the transgenic approach include Golden rice with provitamin A content (Beyer et al, 2002) or soybean with decreased α-linolenic fatty acid content (Flores et al, 2008). Seed oil composition in soybean was also the subject in the study by Haun et al (2014) who have used TALENs to knock-out the fatty acid desaturase 2 (fad2) genes. The enzyme catalyzes the conversion of the monounsaturated oleic acid to the polyunsaturated linoleic acid.…”
Section: " 46mentioning
confidence: 99%
“…Apart from model plant and animal species, studies have been carried out with economically important organisms and promising results have been obtained. However, a majority of the studies have achieved the mutation only at the cellular level and only a few went on to produce a full-grown organism; especially in the case of animals where the process is more complicated and time-consuming (Shukla et al, 2009;Yu et al, 2011;Lillico et al, 2013;Han et al, 2014;Haun et al, 2014;Luo et al, 2014;Wang et al, 2014;Clasen et al, 2015;Proudfoot et al, 2015). The full-grown animals have been reported to live up to several months of age, but it is not clear yet whether they will maintain normal physiological function through to the adulthood (i.e.…”
Section: " 50mentioning
confidence: 99%
See 2 more Smart Citations